2018
DOI: 10.1186/s12872-018-0760-1
|View full text |Cite
|
Sign up to set email alerts
|

Should heart age calculators be used alongside absolute cardiovascular disease risk assessment?

Abstract: BackgroundNational estimates of ‘heart age’ by government health organisations in the US, UK and China show most people have an older heart age than current age. While most heart age calculators are promoted as a communication tool for lifestyle change, they may also be used to justify medication when clinical guidelines advocate their use alongside absolute risk assessment. However, only those at high absolute risk of a heart attack or stroke are likely to benefit from medication, and it is not always clear h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
53
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 35 publications
1
53
1
2
Order By: Relevance
“…(17,18) El análisis conjunto de estos datos en un individuo es el indicador para establecer la necesidad de medicación y de desarrollar hábitos de vida saludables. (19)…”
Section: Resultados Y Discusiónunclassified
“…(17,18) El análisis conjunto de estos datos en un individuo es el indicador para establecer la necesidad de medicación y de desarrollar hábitos de vida saludables. (19)…”
Section: Resultados Y Discusiónunclassified
“…30 There is increasing interest in 'heart age' calculators, which have been promoted around the world including in Australia, New Zealand and the UK. 31 While there are claims that giving patients an 'older' heart age can motivate them to change their lifestyles, a review of biological age formats found no evidence that this is more effective than absolute risk formats. 32 Anecdotally, New Zealand GPs find this to be a useful communication tool to get people interested in their CVD risk and lifestyle change, but absolute risk must be used when considering medication.…”
Section: Communicationmentioning
confidence: 99%
“…Heart age is an ill-defined measure of risk, relative to others of the same age, sex, and ethnicity with optimal risk factor levels. 4,11 As it is not a measure of absolute risk, it is not helpful for medication decisions. 5,11 7.…”
mentioning
confidence: 99%
“…4,11 As it is not a measure of absolute risk, it is not helpful for medication decisions. 5,11 7. There should be evidence from highquality RCTs that screening is effective in reducing mortality or morbidity.…”
mentioning
confidence: 99%
See 1 more Smart Citation